An Analysis Of Figurative Language In “Born For This”, “That’s What You Get” And “The Only Exception” Songs By Paramore - Anjar Dwi Cahyo; Masulah -; Ari Setyorini (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
The analysis provides the study about figurative language, possible meaning and the total meaning in three songs of Paramore, “Born for This”, “That’s What You Get” and “The Only Exception”. This study tries to analyze figurative language, possible meaning and the total meaning in statement of the problem. This analysis aims to analyze the types of figurative language and possible meaning and to tell the total meaning of the Paramore songs. This analysis follows the design of qualitative method because it is related to the object of research. Qualitative description is defines as research designed to produce a low inference description of a phenomenon that draws from discourse.The result of the research of the first song is “Born for This”. This song has figurative language are ambiguity, personification, and etc. “That’s What You Get”song has ambiguity, personification, and etc. “The Only Exception” has personification, metaphor and etc. From this research the researcher concludes, in this songs have many figurative languages to make meaningful.